Desempenho do RTK em rede sob efeito da cintilação ionosférica - Silva, Hérida dos Reis [UNESP] (2014)
Atmospheric effects, especially the ionosphere, are major limiting factors for using high accuracy positioning RTK (Real Time Kinematic) technique. With the distance between the user and the base station, the method efficiency is degraded, since the correlation between the errors is reduced. However, with the use of a network of reference stations the modeling of the errors can be performed this concept is called RTK Network. However, one of the factors degrading the GNSS (Global Navigation Satellite System) signals propagation is the ionospheric scintillation, characterized by rapid changes in the amplitude and phase of the electromagnetic signal passing through irregularities in the electron density of the ionosphere. The occurrence and intensity of scintillation vary according to several factors such as geographic location, seasonality, local time and solar activity. The peak of the Solar Cycle 24 occurred in the summer of 2013 intensified the scintillation effects. Considering the public sector in Brazil, the unique network of reference stations that enables studies about RTK positioning network is located at São Paulo; so called Network GNSS/SP. Currently the network is composed of 20 active stations and a control center for network management using Trimble Pivot (Progressive Infrastructure Via Overlaid Technology)...